Qasam analysis study in Q.s Ad-Dhuha (Perspective Tafsir al-Bayan li al-Qur’an by Bint al-Syathi) - Husna Saniyyah, Syifa (Institut Agama Islam Persis Bandung, 2023)
[Qasam analysis study in Q.s Ad-Dhuha (Perspective Tafsir al-Bayan li al-Qur’an by Bint al-Syathi) This research aims to convey the importance of messages from prophetic revelations, to reveal hidden signals regarding warnings, threats and real truths, expressed in Allah's oaths (Qasam in the al-Qur’an). Providing motivation for Muslims to be active in studying Qasam in the Koran, because when we understand it, our hearts and souls will be moved by the specialness of His word through Qasam in the al-Qur’an. The theory used in this research is Al-Jurjani's nadzam theory which can interpret the beauty of literature in the al-Qur’an with its diversity of meanings and pronunciations. And relevant to the research being prepared by the author. This research method uses qualitative research methods. The data source used is Tafsir al-Bayan li al-Qur'an by Bint al-Syathi and uses secondary data in the form of books that are relevant to the research topic. To obtain this data the author used the library research method, namely reviewing the literature by analyzing, clarifying and presenting the data. According to Bint al-Syathi, this ad-Dhuha letter begins with Qasam with the letter wau. The apparent grandeur is intended to create a powerful attraction. Meanwhile, the selection of muqsam bih is done by drawing attention. The results of this research are Qasam in the Qur'an Q.s Ad-Dhuha from the perspective of the interpretation of Bint al-Syathi, in the treatise on the revelation there are many lessons that can be understood, in the ad-Dhuha letter it is accepted as solace and peace of mind for the Messenger of Allah. , and especially for a Muslim is a definite guide and truth.